Streptomyces sp.: Characterization, Identification and Its Potential as a Ralstonia solanacearum Biological Control Agent in vitro - Saputra, Rachmad; Arwiyanto, Triwidodo; Wibowo, Arif (Talenta Publisher, 2019)
Streptomyces sp. bacteria have the potential to produce antibiotic compounds, which are one of the mechanisms that are widely used in biological control. However, in general, biological control mechanisms also occur through competition, cell wall degradation and induced resistance. This study was aimed to determine the physiological, biochemical and molecular characteristics of two isolates of Streptomyces sp. (S-4 and S16 isolates) isolated from the tomatoes roots, and to find out their ability to control Ralstonia solanacearum, which causes bacterial wilt disease on a wide range of hosts. The results showed both Streptomyces sp. isolates had several different physiological and biochemical characteristics and had a different ability to inhibit R. solanacearum in vitro. Streptomyces sp. S-16 isolate had a high similarity with Streptomyces diastaticus subsp. ardesiacus strain NRRL B-1773T based on the molecular identification results. Further research needs to be done to see the potential inhibition of the two Streptomyces isolates in inhibiting the development of bacterial wilt disease in tomato plants caused by R. solanacearum.